ANALISIS POTENSI WISATA PADA NAGARI KAMANG HILIA KABUPATEN AGAM - Novi Yanita; Rini Eka Sari; Abdiani Khairat Nadra (Ensiklopedia of Journal, 2020)
This research aims to analyze and mapping the tourism potential in Nagari Kamang Hilia in Agam Regency based on 4A Components that are Attraction, accessibility, amenities, and ancillary services. Nagari Kamang Hilia has natural beauty such as hills, cave, river, forest and also farming land such as rice field, cocoa, dragon fruit, orange, durian and cassava. The study used qualitative approach. Data collecting is obtained by conducting observation, in depth interview, and documentation study. The data is then analyzed by using triangulation, comparing the results of observation, in depth interview and documentation study. The research finding reveals that there are some villages in Nagari Kamang Hilia that have tourism potentials in the form of natural attractions, cultural and artificial attractions. The accessibility also categorized as in good condition, for ancillary service, Nagari Kamang Hilia had formed “Kelompok Sadar Wisata (POKDARWIS)” and Kamang Hilia Tourism Lovers Community (KOMPPHIL) as the management and tourism activists. Meanwhile, the amenities in Nagari Kamang Hilia still limited. Tourism potentials in Nagari Kamang Hilia can develop as natural tourism in the form of rural tourism and special interest tourism and also cultural tourism.